Ensino de ciências, realidade aumentada e o aplicativo sophus: uma experiência numa escola do campo (assú/rn) - Morais, Paulo Henrique de (Universidade Federal Rural do Semi-Árido, 2019)
Digital Information and Communication Technologies (TDICs) are increasingly present in our daily lives and can be defined as the area that uses digital technological tools in order to facilitate communication with a specific audience. In this sense, this work aimed to investigate whether the Sophus Augmented Reality application can be a purposeful educational tool for teaching and learning science in elementary school II. To respond to this objective, the research specifically sought to: 1) Investigate educational experiences in a rural school; 2) Analyze the potentialities of the Sophus Application for Science Education. The research took place in the three ninth grade classes of Monsenhor Alves Júlio Bezerra Municipal School, located in the Rural Community of Nova Esperança, a rural school in the municipality of Assú / RN. As the theoretical basis of our work, we adopted authors such as: Fernandes and Molina (sd), who deal with Rural Education and who, in our text, contributed with the concepts of Rural Education and rural education, in which we performed a brief discussion of their distinction; Souza and Camargo (2011), who discuss about the Human Body, contributing to conceptualize the body, not only as a biological factor, but also as a body constituted by the social spaces that individuals frequent; Kirner and Kirner (2011), talk about TDICs, especially Virtual Reality - VR and Augmented Reality - RA; Marconi and Lakatos (2013), supported the discussion about field research. As a methodological resource we carry out a field research, bibliographical research and action research. In addition to documentary research in the municipal and state departments of education, we adopted as a data collection tool the questionnaire and participant observation, in order to identify students' knowledge about Technologies, ICTs, TDICs and RA. We applied specific questionnaires about the Respiratory System, the Bone and Muscle Systems and the Sensory System, one in each of the research participants. We use traditional teaching method-based learning sequences and TDIC Smartphone-based learning sequences to compare responses before and after using the application. We came to the conclusion that TDICs, specifically the RA Sophus app, contribute to the science teaching and learning process, since from the use of it in the mentioned classes we could realize that the students performed better, both in interaction during class and learning performance.
Keywords: Tecnologias digitais de informação e comunicação; Realidade aumentada; Ensino de ciências; Aprendizagem; Digital Information and communication technologies.; Augmented reality; Science teaching.; Learning; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES